The Impact of Decentralizing HIV Services on Patients at St. Elizabeth Hospital Shisong, Cameroon - Nkengfua, Blaise; Fobellah, Nkengafac Nyiawung; Atanga, Sylvester Ndeso; Fobellah, Belleh Nyiawung (Archives of Clinical and Biomedical Research, 2021)
Background: Cameroon is one of the global health priority countries. Without decentralization of HIV services from physicians to nurses and midwives, the sustainable scale up of antiretroviral therapy (ART) in resource limited settings may not be possible; this is a key consideration in achieving epidemic control. Until 2005, policy allowed only physicians to prescribe antiretroviral therapy to HIV infected persons which delayed care delivery. Objective: In October 2014 there was effective implementation of option B+ strategy. We intended to compare antiretroviral therapy (ART) uptake, Retention to ART, and male partner participation (MAP) in Prevention of Mother to Child Transmission of HIV (PMTCT) pre and post B+ implementation, following change in staffing policy. Design: A retrospective chart review study in which routine program data was collected from PMTCT and HIV Management unit (HMU). Methods: We evaluated ART Uptake, retention to ART and Male partner participation (MAP) in PMTCT pre (December 2011 to November 2014) and post (December 2014 to November 2017). Results: A total of 2958 (pre) and 2696 (post) women presented to antenatal care (ANC). Of the 284 women who tested HIV positive, A majority was treated post task shifting, pre 111 (60.22%) vs. post; 173 (92.7%). The average 6 and 12 months retention rates of clients to ART was 57 (89.49) and 48 (84.21%) at ANC post B+, similarly, at HMU we saw an insignificantly change in the number of clients retained at 6 and 12 months on ART pre B+, (Pre 85.735% vs. Post 80.93 p-value 0.045< 0.5). MAP pre/post was [105 (3.55%) vs. 272 (10.09%) P-value =0.266]. Conclusions: A considerable growth in ART uptake was seen at PMTCT/ANC only following task sharing. The retention rates for both pregnant, breastfeeding women and all ages was approximately the same 85% which is